Municipal Solid Waste Generation and Management: A Case Study of Rangpur City Corporation (Journal of Bangladesh Institute of Planners, 2016)
According to Conservancy Authority of Rangpur City Corporation (RCC), about 13 tons of waste is generated daily. About 77 percent waste is nationally compostable in nature. The RCC has no recycling arrangement of its own. However, 151 dustbins were found in different points of 15 wards in RCC, most of those are in bad condition. The ‘Nachnia Beel’ is a legally recognized waste disposal site for RCC which has no environmental clearance. The survey for this study in 2015 reveals that in RCC many people have no proper idea on municipal Solid Waste Management (SWM). A large number of people drop their waste beside the road and the rest of them manage it personally. Clinical and industrial wastes are not managed by RCC. In spite of containing 151 dustbins, maximum women cannot drop their waste in dustbins due to distance and miserable dirty condition of the dustbin site. Apparently, it is not possible to remove all the solid waste, but it is possible to reduce the bad effect of solid waste by an improved waste management system with public-private partnership.JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 171-182